Ultraviolet curable coating composition

By using compositions such as trifunctional urethane (meth)acrylate oligomers, the problem of insufficient scratch resistance of UV coatings on flexible sheets has been solved, and the scratch resistance, adhesion, gloss and workability have been improved, making it suitable for surface coating of LVT flooring materials.

CN120981531APending Publication Date: 2025-11-18KCC CORP
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202480023024.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-04-14
Filing Date
2024-04-09
Publication Date
2025-11-18

AI Technical Summary

Technical Problem

Existing UV coating compositions are prone to cracking on flexible sheets and suffer from reduced scratch resistance, heat resistance, and heat resistance.

Method used

A combination of trifunctional urethane (meth)acrylate oligomers, trifunctional or higher (meth)acrylate monomers, difunctional (meth)acrylate monomers, monofunctional (meth)acrylate monomers, ceramic beads, and photoinitiators is used to form a UV-curable coating composition with excellent scratch resistance.

Benefits of technology

It improves the scratch resistance, adhesion, gloss and workability of the coating, forms a uniform coating, and is suitable for coating the surface of LVT flooring materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005618321970000081
    Figure BDA0005618321970000081
  • Figure BDA0005618321970000091
    Figure BDA0005618321970000091
  • Figure BDA0005618321970000092
    Figure BDA0005618321970000092
Patent Text Reader

Abstract

The present invention relates to an ultraviolet-curable coating composition comprising a trifunctional urethane (meth) acrylate oligomer, a trifunctional or higher (meth) acrylate monomer, a bifunctional (meth) acrylate monomer, a monofunctional (meth) acrylate monomer, a ceramic bead, and a photoinitiator, and more specifically, to an ultraviolet-curable coating composition comprising a trifunctional urethane (meth) acrylate oligomer, a trifunctional or higher (meth) acrylate monomer, a bifunctional (meth) acrylate monomer, a monofunctional (meth) acrylate monomer, a ceramic bead, and a photoinitiator, the trifunctional urethane (meth) acrylate oligomer has a weight average molecular weight of 800 to 3,000 g / mol, and the ceramic beads have an average particle size of 7 to 13 [mu] m. The UV-curable coating composition has excellent stain resistance, adhesiveness, gloss, workability, and scratch resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a UV-curable coating composition with excellent stain resistance, adhesion, gloss, workability and scratch resistance. Background Technology

[0002] To improve the scratch resistance of flooring materials such as ceramic tiles and facilitate the removal of surface contaminants, various UV coating techniques have been proposed. For example, Korean Patent No. 0103647, US Patent Nos. 3,782,961 and 3,912,516 disclose coating compositions containing photocurable oligomers. However, these conventional coating compositions are unsuitable for coating flexible molded products. When applied to flexible sheets such as polyvinyl chloride (PVC), they suffer from cracking due to a lack of flexibility. Furthermore, while enhancing flexibility, they result in reduced scratch resistance and heat resistance.

[0003] Recently, while UV coatings for LVT (Luxury Vinyl Tile) offer excellent stain resistance, adhesion, and workability, they suffer from poor scratch resistance. Therefore, there is a need to develop a coating composition for flooring materials that possesses excellent stain resistance, adhesion, gloss, and workability, as well as superior scratch resistance. Summary of the Invention

[0004] (The problem the invention aims to solve)

[0005] This invention provides a UV-curable coating composition with excellent stain resistance, adhesion, gloss, workability and scratch resistance.

[0006] (The measures taken to solve the problem)

[0007] The present invention provides an ultraviolet-curable coating composition comprising a trifunctional urethane (meth)acrylate oligomer, a trifunctional or higher (meth)acrylate monomer, a difunctional (meth)acrylate monomer, a monofunctional (meth)acrylate monomer, ceramic beads, and a photoinitiator.

[0008] (The effect of the invention)

[0009] This invention provides a UV-curable coating composition with excellent stain resistance, adhesion, gloss, workability, and scratch resistance. The coating composition of this invention improves upon the problem of decreased scratch resistance in conventional coatings and forms a uniform coating film, thereby providing stable physical properties such as excellent stain resistance, adhesion, gloss, scratch resistance, and workability. The coating composition of this invention can be used as a coating for surface application of flooring materials such as LVT (Luxury Vinyl Tile). Detailed Implementation

[0010] The present invention will now be described in detail. However, the present invention is not limited to the following, and the constituent elements may be varied or selectively combined as needed. Therefore, it should be understood that the present invention includes all modifications, equivalents, and even substitutions contained within its concept and technical scope.

[0011] The "weight-average molecular weight" used in this specification is a value determined by conventional methods known in the art, such as GPC (gel permeation chromatograph). "Viscosity" is a value determined by conventional methods known in the art, such as using a Brookfield viscometer at room temperature (25°C). Functional group valences, such as "acid value," are values ​​determined by conventional methods known in the art, such as titration. "Average particle size" is a value determined by conventional methods known in the art, such as using a laser particle size analyzer.

[0012] The UV-curable coating composition according to the present invention comprises a trifunctional urethane (meth)acrylate oligomer, a trifunctional or higher (meth)acrylate monomer, a difunctional (meth)acrylate monomer, a monofunctional (meth)acrylate monomer, ceramic beads, and a photoinitiator. When the trifunctional urethane (meth)acrylate oligomer with a weight-average molecular weight of 800 to 3,000 g / mol is used, and the ceramic beads with an average particle size of 7 to 13 μm are used, the dispersibility of the ceramic beads in the coating composition becomes excellent, and the drying rate and surface tension of the coating film are adjusted, thereby allowing the ceramic beads to be uniformly coated on the coating film surface. As a result, the scratch resistance of the formed coating film is improved, and excellent appearance properties are achieved.

[0013] As needed, the coating composition of the present invention may further include additives commonly used in the field of UV-curable coatings, such as adhesion promoters, dispersants, slip agents and defoamers, surface conditioners, polymerization inhibitors, and matting agents.

[0014] Trifunctional carbamate (meth) acrylate oligomers

[0015] The UV-curable coating composition of the present invention comprises trifunctional urethane (meth)acrylate oligomers. As the main component of the dried coating film, the trifunctional urethane (meth)acrylate oligomers can improve scratch resistance, stain resistance, adhesion, etc.

[0016] The weight-average molecular weight (Mw) of the trifunctional urethane (meth)acrylate oligomer can be from 800 to 3,000 g / mol, for example, from 1,000 to 2,500 g / mol. When the weight-average molecular weight of the trifunctional urethane (meth)acrylate oligomer is within the aforementioned range, it exhibits excellent compatibility with ceramic beads and increases the crosslinking density of the coating film, thereby improving scratch resistance, appearance, and adhesion. When the weight-average molecular weight of the trifunctional urethane (meth)acrylate oligomer is less than the aforementioned range, the viscosity is too low, resulting in decreased stain resistance and gloss of the coating film. When it exceeds the aforementioned range, the crosslinking density increases significantly, leading to decreased elasticity of the coating film, and thus reduced adhesion, stain resistance, and scratch resistance.

[0017] The viscosity (at 25°C) of the trifunctional urethane (meth)acrylate oligomer can be from 500 to 3,000 cps, for example, from 900 to 2,000 cps. When the viscosity of the trifunctional urethane (meth)acrylate oligomer is within the aforementioned range, the workability is excellent, improving appearance and adhesion. When the viscosity of the urethane (meth)acrylate oligomer is below the aforementioned range, the viscosity is too low, resulting in no coating film formation or decreased adhesion and iodine resistance of the coating film. When the viscosity exceeds the aforementioned range, the workability of the coating becomes inferior, thereby reducing the appearance and scratch resistance of the coating film.

[0018] As needed, the trifunctional urethane (meth)acrylate oligomer can also be mixed with reactive oligomers, such as polyester (meth)acrylate oligomers. In this case, the curability, moisture resistance, thermal cycling resistance, and heat resistance of the coating film are improved, and the leveling, workability, adhesion, and flexibility of the coating composition are further improved.

[0019] The content of the trifunctional urethane (meth)acrylate oligomer, based on the total weight of the coating composition, can be 30 to 60% by weight, for example, 40 to 50% by weight. When the content of the trifunctional urethane (meth)acrylate oligomer is within the aforementioned range, an appropriate crosslinking density can be maintained, thereby improving the curability, moisture resistance, iodine resistance, and scratch resistance of the coating film. When the content of the trifunctional urethane (meth)acrylate oligomer is less than the aforementioned range, the viscosity is low, resulting in a decrease in crosslinking density and curability, thus reducing scratch resistance and adhesion. When the content exceeds the aforementioned range, the viscosity of the composition is high, resulting in poor workability, and thus reducing the appearance and gloss of the coating film.

[0020] (meth)acrylate monomers

[0021] The UV-curable coating composition of the present invention comprises (meth)acrylate monomers. As an auxiliary component for drying the coating film, the (meth)acrylate monomers improve the flowability, leveling, and workability of the coating composition, while also enhancing the iodine resistance, scratch resistance, and adhesion of the coating film. In particular, the (meth)acrylate monomers can replace solvents to increase the hardness and cured density of the coating film, mitigating issues such as viscosity increase during application and the generation of VOCs and odors.

[0022] The (meth)acrylate monomers comprise trifunctional or higher (meth)acrylate monomers, difunctional (meth)acrylate monomers, and monofunctional (meth)acrylate monomers. The UV-curable coating composition of the present invention, by using two highly functional monomers in combination, increases the crosslinking density of the coating film, thereby providing improved stain resistance and scratch resistance. Furthermore, by using monofunctional (meth)acrylate monomers in combination, the viscosity of the coating can be easily adjusted, and adhesion and flexibility can be further improved.

[0023] Trifunctional or higher (meth)acrylate monomers

[0024] Trifunctional or higher (meth)acrylate monomers are (meth)acrylate monomers having three or more polymerizable functional groups, such as three to six, or three or four, as polymerizable unsaturated groups, which improve the scratch resistance of the coating and reduce the shrinkage of the coating.

[0025] Non-limiting examples of the trifunctional or higher (meth)acrylate monomers include: trimethylolpropane tri(meth)acrylate, pentaerythritol tri(meth)acrylate, and other trifunctional (meth)acrylate monomers; pentaerythritol tetra(meth)acrylate, di(trimethylolpropane)tetra(meth)acrylate, and other tetrafunctional (meth)acrylate monomers; dipentaerythritol poly(meth)acrylate, etc., which can be used alone or in combination of two or more. As an example, the trifunctional or higher (meth)acrylate monomer can be a trifunctional (meth)acrylate monomer, such as trimethylolpropane tri(meth)acrylate.

[0026] The molecular weight of the trifunctional or higher (meth)acrylate monomer can be from 100 to 500 g / mol, for example, from 200 to 400 g / mol. When the molecular weight of the trifunctional or higher (meth)acrylate monomer is within the aforementioned range, the crosslinking density of the coating composition increases, thereby improving stain resistance, gloss, and adhesion. When the molecular weight of the trifunctional or higher (meth)acrylate monomer is less than the aforementioned range, the crosslinking efficiency and intermolecular bonding force decrease, and the iodine resistance and heat resistance decrease. When it exceeds the aforementioned range, the curing reaction slows down, and the adhesion decreases.

[0027] The viscosity (at 25°C) of the trifunctional or higher-grade (meth)acrylate monomer can be from 50 to 300 cps, for example, from 80 to 120 cps. When the viscosity of the trifunctional or higher-grade (meth)acrylate monomer is within the aforementioned range, an appropriate viscosity of the coating composition can be maintained, thereby improving appearance, gloss, workability, and adhesion. When the viscosity of the trifunctional or higher-grade (meth)acrylate monomer is less than the aforementioned range, the viscosity is too low, resulting in no coating film formation or decreased adhesion and heat resistance of the coating film. When it exceeds the aforementioned range, the workability of the coating deteriorates, and the appearance deteriorates.

[0028] The content of the trifunctional or higher-grade (meth)acrylate monomers, based on the total amount of the coating composition, can be 2 to 15% by weight, for example, 5 to 10% by weight. When the content of the trifunctional or higher-grade (meth)acrylate monomers is within the aforementioned range, the crosslinking density of the coating composition increases, thereby improving stain resistance, gloss, and adhesion. When the content of the trifunctional or higher-grade (meth)acrylate monomers is less than the aforementioned range, the viscosity is low, thereby reducing the crosslinking density, and decreasing the degree of crosslinking, adhesion, and scratch resistance. When the content exceeds the aforementioned range, the viscosity is too high, thereby reducing the flexibility of the coating film, and thus reducing gloss and appearance.

[0029] Difunctional (meth)acrylate monomers

[0030] The use of a mixture of difunctional (meth)acrylate monomers and trifunctional or higher (meth)acrylate monomers to replace solvents can improve coating shrinkage.

[0031] The difunctional (meth)acrylate monomer may be, for example, hexanediol dimethacrylate, polyethylene glycol dimethacrylate, glycerol dimethacrylate, diethylene glycol dimethacrylate, triethylene glycol dimethacrylate, dipropylene glycol dimethacrylate, tripropylene glycol dimethacrylate, tetraethylene glycol dimethacrylate, and other alkylene glycol dimethacrylate monomers. As an example, the difunctional (meth)acrylate monomer may be tripropylene glycol dimethacrylate.

[0032] The molecular weight of the difunctional (meth)acrylate monomer can be from 150 to 450 g / mol, for example, from 250 to 350 g / mol. When the molecular weight of the difunctional (meth)acrylate monomer is within the aforementioned range, the crosslinking density of the coating composition increases, which improves stain resistance, gloss, and adhesion. When the molecular weight of the difunctional (meth)acrylate monomer is less than the aforementioned range, the crosslinking efficiency decreases, and the iodine resistance and appearance decrease. When it exceeds the aforementioned range, the crosslinking density increases significantly, the elasticity of the coating film decreases, and the appearance, adhesion, and heat resistance decrease.

[0033] The viscosity (at 25°C) of the difunctional (meth)acrylate monomer can be 5 to 30 cps, for example, 15 to 20 cps. When the viscosity of the difunctional (meth)acrylate monomer is within the aforementioned range, it maintains an appropriate viscosity of the coating composition, thereby improving appearance, gloss, workability, and adhesion. When the viscosity of the difunctional (meth)acrylate monomer is less than the aforementioned range, the viscosity is too low, and the heat resistance of the coating film will decrease. When it exceeds the aforementioned range, the workability of the coating deteriorates, and the appearance will decline.

[0034] The content of the difunctional (meth)acrylate monomer, based on the total amount of the coating composition, can be 1 to 10% by weight, for example, 2 to 7% by weight. When the content of the difunctional (meth)acrylate monomer is within the aforementioned range, the crosslinking density of the coating composition increases, which improves stain resistance, gloss, and adhesion. When the content of the difunctional (meth)acrylate monomer is less than the aforementioned range, the viscosity of the coating composition increases, thereby reducing flowability and leveling properties. When it exceeds the aforementioned range, the viscosity of the composition is very low, thereby reducing curability, and therefore reducing workability and adhesion.

[0035] Monofunctional (meth)acrylate monomers

[0036] Monofunctional (meth)acrylate monomers play a role in adjusting the viscosity of coatings and increasing film shrinkage.

[0037] The monofunctional (meth)acrylate monomer may be, for example, 2-ethylhexyl (meth)acrylate, octyldecyl (meth)acrylate, stearyl (meth)acrylate, docosyl (meth)acrylate, tridecyl (meth)acrylate, nonylphenol ethoxylate mono(meth)acrylate, β-carboxyethyl (meth)acrylate, isobornyl (meth)acrylate, tetrahydrofurfuryl (meth)acrylate, 4-butylcyclohexyl (meth)acrylate, dicyclopentenyl (meth)acrylate, dicyclopentenoxyethyl (meth)acrylate, ethoxyethoxyethyl (meth)acrylate, ethoxylated mono(meth)acrylate, 2-hydroxyethyl (meth)acrylate, and 2-hydroxypropyl (meth)acrylate. As an example, the monofunctional (meth)acrylate monomer may be 2-hydroxypropyl (meth)acrylate.

[0038] The molecular weight of the monofunctional (meth)acrylate monomer can be from 50 to 300 g / mol, for example, from 100 to 200 g / mol. When the molecular weight of the monofunctional (meth)acrylate monomer is within the aforementioned range, the crosslinking density of the coating composition increases, which improves stain resistance, gloss, and adhesion. When the molecular weight of the monofunctional (meth)acrylate monomer is less than the aforementioned range, the crosslinking efficiency decreases, and the iodine resistance and appearance decrease. When it exceeds the aforementioned range, the crosslinking density increases significantly, thereby reducing the elasticity of the coating film, and thus reducing the appearance, adhesion, and heat resistance.

[0039] The viscosity (at 25°C) of the monofunctional (meth)acrylate monomer can be from 5 to 25 cps, for example, from 10 to 15 cps. When the viscosity of the monofunctional (meth)acrylate monomer is within the aforementioned range, the appropriate viscosity of the coating composition can be maintained, thereby improving appearance, gloss, workability, and adhesion. When the viscosity of the monofunctional (meth)acrylate monomer is less than the aforementioned range, the viscosity is too low, thereby reducing the workability and stain resistance of the coating film. When it exceeds the aforementioned range, the workability of the coating deteriorates, thereby reducing appearance and gloss.

[0040] The content of the monofunctional (meth)acrylate monomer, based on the total amount of the coating composition, can be 10 to 40% by weight, for example, 20 to 30% by weight. When the content of the monofunctional (meth)acrylate monomer is within the aforementioned range, the crosslinking density of the coating composition increases, thereby improving stain resistance, gloss, and adhesion. When the content of the monofunctional (meth)acrylate monomer is less than the aforementioned range, the viscosity of the coating composition increases, and the dilutionability decreases. When it exceeds the aforementioned range, the viscosity of the composition is very low, thereby reducing curing properties and scratch resistance.

[0041] As an example, the trifunctional or higher (meth)acrylate monomers, the difunctional (meth)acrylate monomers, and the monofunctional (meth)acrylate monomers can be mixed in a weight ratio of 1:0.2 to 1:2 to 5, for example, in a weight ratio of 1:0.3 to 0.8:3 to 4. When the monomers are used in the aforementioned ratio, appropriate viscosity can be maintained and curing properties can be improved, thereby improving the coating's resistance to iodine, scratch resistance, stain resistance, adhesion, and other physical properties. Furthermore, the viscosity adjustment and odor improvement effects during operation are further enhanced.

[0042] Ceramic beads

[0043] The UV-curable coating composition of the present invention comprises spherical ceramic beads. The ceramic beads further enhance the scratch resistance of the coating film.

[0044] The ceramic beads can be alkali aluminosilicate ceramic beads, zirconia ceramic beads, alumina ceramic beads, etc. For example, the ceramic beads can be alkali aluminosilicate ceramic beads.

[0045] When amorphous ceramic beads are used as the ceramic beads, the ceramic beads protrude from the coating surface, resulting in a decrease in the appearance and gloss of the coating, as well as a decrease in the hardness and scratch resistance of the manufactured coating. On the other hand, when spherical ceramic beads are used and the coating is formed with a thickness equal to the average particle size of the ceramic beads, the spherical ceramic beads within the coating increase the resistance to external impact, thereby improving the scratch resistance of the coating.

[0046] The average particle size of the ceramic beads can be 7 to 13 μm, for example, 9 to 11 μm. When the average particle size of the ceramic beads is within the aforementioned range, the compatibility with urethane (meth)acrylate oligomers increases, thereby improving scratch resistance and adhesion. When the average particle size of the ceramic beads is less than the aforementioned range, the porosity is low, resulting in decreased bonding with oligomers and monomers, thus reducing scratch resistance and appearance. When the average particle size exceeds the aforementioned range, the porosity is high, resulting in a decreased appearance and excessively increased surface roughness, thus reducing adhesion and stain resistance.

[0047] The content of the ceramic beads, based on the total weight of the coating composition, can be 1 to 8% by weight, for example, 2 to 6% by weight. When the content of the ceramic beads is within the aforementioned range, the compatibility with the urethane (meth)acrylate oligomer increases, thereby improving scratch resistance and adhesion. When the content of the ceramic beads is less than the aforementioned range, the crosslinking density with the urethane (meth)acrylate oligomer is low, resulting in decreased stain resistance and scratch resistance when forming a coating film. When the content exceeds the aforementioned range, storage stability and workability decrease due to the reaction with the coating composition.

[0048] Photoinitiator

[0049] The UV-curable coating composition of the present invention contains a photoinitiator. A photoinitiator is a component that initiates photopolymerization by being excited by ultraviolet light or the like, and any photoinitiator commonly known in the art can be used without restriction.

[0050] Non-limiting examples of photoinitiators that may be used include, for example, MICURE BP, JRCURE MBF, JRCURE 184, Irgacure 184, Irgacure 369, Irgacure 651, Irgacure 819, Irgacure 907, Benzionalkylether, Benzophenone, Benzyl dimethylkatal, Hydroxycyclohexyl phenylacetone, Chloroacetophenone, 1,1-Dichloroacetophenone, Diethoxyacetophenone, and Hydroxyacetophenone. Acetophenone, 2-chlorothioxanthone, 2-ethylanthraquinone (2-ETAQ(2-EthylAnthraquinone)), 1-hydroxy-cyclohexylphenyl-ketone, 2-hydroxy-2-methyl-1-phenyl-1-propanone, 2-hydroxy-1-[4-(2-hydroxyethoxy)phenyl]-2-methyl-1-propanone, methylbenzoylformate, bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide, 2-hydroxy-2-methyl-1-phenylpropane-1-one, etc. These can be used alone or in combination of two or more.

[0051] The maximum absorption wavelength of the photoinitiator is not particularly limited as long as it can absorb ultraviolet light, for example, it can be in the range of 200 to 410 nm.

[0052] For example, the photoinitiator may comprise: a first photoinitiator with a melting point of 40 to 55°C, for example 47 to 49°C; a second photoinitiator with a melting point of 65 to 80°C, for example 70 to 75°C; and a third photoinitiator with a melting point of 30 to 65°C, for example 40 to 55°C. When the aforementioned three photoinitiators are included, the coating strength and adhesion will be improved due to proper curing with the ceramic beads.

[0053] The content of the photoinitiator, based on the total amount of the coating composition, can be from 0.01 to 10% by weight, for example, from 0.1 to 6% by weight. As an example, based on the total amount of the coating composition, it may contain: 0.1 to 3% by weight of the first photoinitiator, for example, 0.5 to 2% by weight; 0.1 to 5% by weight of the second photoinitiator, for example, 1 to 3% by weight; and 0.01 to 2% by weight of the third photoinitiator, for example, 0.1 to 1% by weight. If the content of the photoinitiator is less than the aforementioned range, the coating strength and adhesion will decrease due to reduced curability or no curing, and wrinkles will occur due to uncured coatings. On the other hand, if the content of the photoinitiator exceeds the aforementioned range, contamination may occur due to unreacted photoinitiators, or decreased adhesion may occur due to low polymerization.

[0054] additive

[0055] In addition to the aforementioned components, the coating compositions according to the present invention may selectively further include additives commonly used in the art, depending on the intended use and environment of the coating composition. As an example, the coating compositions of the present invention may, as needed, further include additives such as adhesion promoters, dispersants, slip agents and defoamers, surface conditioners, polymerization inhibitors, and matting agents.

[0056] As the adhesion promoter, any adhesion promoter known in the art can be used without particular limitation, such as acid esters, polyester resins, mixtures thereof, etc. As an example, an acid ester with an acid value of 120 to 180 mg KOH / g and a specific gravity of 110 to 120 can be used. As another example, a polyester resin with a viscosity (23°C) of 9,000 cps and a solid content of 50% can be used.

[0057] The dispersant can be any dispersant known in the art, without particular limitation. For example, pigment wetting and dispersing agents, dispersing agents that act as both wetting and dispersing agents, mixtures thereof, etc., can be used.

[0058] The slip agent and defoamer can be any slip agents and defoamers known in the art, without particular limitation; for example, organosilicon acrylates can be used.

[0059] As the surface conditioner, any surface conditioner known in the art can be used without particular limitation; for example, slip agents and anti-blocking agents can be used. For instance, polyether siloxanes can be used.

[0060] The matting agent serves to adjust the viscosity and gloss of the coating composition, and is not particularly limited to any agent known in the art. For example, silica can be used.

[0061] The content of each additive is not particularly limited; for example, it can be from 0.01 to 20% by weight, based on the total amount of the coating composition.

[0062] The method for manufacturing the coating composition of the present invention is not particularly limited. For example, it can be manufactured by conventional methods that involve adding the aforementioned trifunctional urethane (meth)acrylate oligomer, trifunctional or higher (meth)acrylate monomer, difunctional (meth)acrylate monomer, monofunctional (meth)acrylate monomer, ceramic beads and photoinitiator, along with additives as needed, into a mixing device such as a solvent or a mixer, and then mixing them at an appropriate temperature (e.g., room temperature).

[0063] (Method of implementing the invention)

[0064] The present invention will be described in more detail below through embodiments. However, the following embodiments are intended to help understand the present invention and are not intended to limit the scope of the present invention in any way to the embodiments.

[0065] [Examples 1-17]

[0066] The UV-curable coating compositions of each embodiment were prepared according to the compositions described in Tables 1 and 2 below.

[0067] [Comparative Examples 1-9]

[0068] According to the compositions described in Table 3 below, UV-curable coating compositions for each comparative example were prepared.

[0069] [Table 1]

[0070]

[0071]

[0072] [Table 2]

[0073]

[0074]

[0075] [Table 3]

[0076]

[0077]

[0078] A-1: Trifunctional urethane acrylate oligomer (Mw 1,760 g / mol, viscosity (25°C) 1,200 cps)

[0079] A-2: Trifunctional urethane acrylate oligomer (Mw 910 g / mol, viscosity (25℃) 750 cps)

[0080] A-3: Trifunctional urethane acrylate oligomer (Mw 2,730 g / mol, viscosity (25°C) 2,030 cps)

[0081] A-4: Trifunctional urethane acrylate oligomer (Mw 720 g / mol, viscosity (25℃) 476 cps)

[0082] A-5: Trifunctional urethane acrylate oligomer (Mw 3,090 g / mol, viscosity (25°C) 3,120 cps)

[0083] B-1: Trifunctional acrylate monomer (trimethylolpropane triacrylate, molecular weight 296, viscosity (25℃) 105cps)

[0084] B-2: Difunctional acrylate monomer (tripropylene glycol diacrylate, molecular weight 300, viscosity (25℃) 17cps)

[0085] B-3: Monofunctional acrylate monomer (2-hydroxypropyl acrylate, molecular weight 130, viscosity (25℃) 12cps)

[0086] C-1: Ceramic beads (alkaline aluminosilicate particles with an average size of 10μm)

[0087] C-2: Ceramic beads (alkaline aluminosilicate particles with an average size of 8μm)

[0088] C-3: Ceramic beads (alkaline aluminosilicate particles with an average size of 12μm)

[0089] C-4: Ceramic beads (alkaline aluminosilicate particles with an average size of 5μm)

[0090] C-5: Ceramic beads (alkaline aluminosilicate particles with an average size of 15μm)

[0091] D-1: Photoinitiator 1 (benzophenone)

[0092] D-2: Photoinitiator 2 (methyl benzoylformate)

[0093] D-3: Photoinitiator 3 (1-hydroxy-cyclohexyl-phenyl-one)

[0094] E: Adhesion promoter (polyester resin, Tego Variplus 3350UV, EVONIK).

[0095] F: Dispersant (Dispers 670, EVONIK)

[0096] G: Surface conditioner (silicone acrylate, RAD2500, EVONIK)

[0097] H: Polymerization inhibitor (Eastman Hydroquinone, Eastman Corporation)

[0098] I: Matting agent (white colored micronized silica gel, SS SIL-375, S-Chemtech)

[0099] [Physical Property Evaluation]

[0100] The physical properties of the UV-curable coating compositions prepared according to the various examples and comparative examples were determined by the following methods, and the results are shown in Tables 4 to 6 below.

[0101] Sample preparation

[0102] The coating compositions of each example and comparative example were coated (thickness: 10-15 μm) onto PVC flooring material and then photocured (light intensity: 2,000 mJ / cm²). 2 Light intensity: 140mW / cm 2 To prepare the sample.

[0103] Appearance

[0104] Each sample is visually inspected to check for defects such as roll marks, dewetting, and orange peel, and is rated as excellent (◎), good (○), fair (△), or poor (×).

[0105] Curing properties

[0106] At 2,000 mJ / 100 mW / cm 2 After curing the sample under the specified conditions, observe its appearance and evaluate it as excellent (◎), good (○), fair (△), or poor (×).

[0107] Adhesion

[0108] The cross-cut tape test was performed according to ASTM D3359. Using a cross cutter, 100 marks were made on a 1mm x 1mm surface (10 marks horizontally and 10 marks vertically). Nichiban tape was applied and then removed. The number of marks where the coating adhered was maintained was counted. Adhesion was evaluated according to the following criteria.

[0109] [Evaluation Criteria]

[0110] Excellent (◎): Maintains coating adhesion at 99 or higher.

[0111] Good (○): 95 or more but less than 99 marks maintains coating adhesion.

[0112] General (△): 85 or more but less than 95 grid lines maintain coating adhesion.

[0113] Defective (×): Less than 85 grid squares to maintain coating adhesion

[0114] Stain resistance

[0115] Apply an oil-based pen to each sample, and confirm the wiping performance after 5 minutes, and evaluate it as excellent (◎), good (○), fair (△), or poor (×).

[0116] luster

[0117] The gloss of each sample was measured using a glossmeter (60 degrees) and rated as excellent (◎), good (○), fair (△), or poor (×).

[0118] Scratch resistance

[0119] The degree of coating damage was observed according to the EN16094 test method, and scratch resistance was evaluated according to the following standards.

[0120] Excellent (◎): No scratches

[0121] Good (○): 1 or more but less than 10 scratches detected

[0122] General (△): 10 or more but less than 30 scratches identified.

[0123] Defective (×): More than 30 scratches detected

[0124] [Table 4]

[0125]

[0126] [Table 5]

[0127]

[0128]

[0129] [Table 6]

[0130]

[0131] The results in Tables 4 to 6 above confirm that the UV-curable coating compositions of Examples 1-17 according to the present invention exhibit excellent physical properties in all measured items. However, the UV-curable coating compositions of Comparative Examples 1-9, which deviate from the compositions of the present invention, exhibited inferior physical properties overall compared to the examples.

[0132] Specifically, the UV-curable coating composition of Comparative Example 1, which used a trifunctional urethane (meth)acrylate oligomer but had a weight-average molecular weight below the lower limit of the scope of this invention (A-4), exhibited inferior curing properties, stain resistance, and gloss. On the other hand, the UV-curable coating composition of Comparative Example 2, which used a trifunctional urethane (meth)acrylate oligomer but had a weight-average molecular weight exceeding the upper limit of the scope of this invention (A-5), exhibited inferior appearance, curing properties, stain resistance, and scratch resistance.

[0133] Although ceramic beads were used, the UV-curable coating composition of Comparative Example 3, which used ceramic beads with an average particle size lower than the lower limit of the scope of the present invention (C-3), exhibited disadvantages in appearance, gloss, and scratch resistance. On the other hand, the UV-curable coating composition of Comparative Example 4, which used ceramic beads with an average particle size exceeding the upper limit of the scope of the present invention (C-4), exhibited disadvantages in appearance, adhesion, and stain resistance.

[0134] The UV-curable coating composition of Comparative Example 5, which does not contain the trifunctional urethane (meth)acrylate oligomer according to the present invention, exhibits disadvantages in appearance, stain resistance, gloss, and scratch resistance. Furthermore, the UV-curable coating composition of Comparative Example 6, which does not contain trifunctional or higher-functional (meth)acrylate monomers according to the present invention, exhibits disadvantages in curing properties and adhesion; the UV-curable coating composition of Comparative Example 7, which does not contain difunctional (meth)acrylate monomers according to the present invention, exhibits disadvantages in curing properties, stain resistance, and gloss; and the UV-curable coating composition of Comparative Example 8, which does not contain monofunctional (meth)acrylate monomers according to the present invention, exhibits disadvantages in appearance, curing properties, adhesion, and gloss. The UV-curable coating composition of Comparative Example 9, which does not contain ceramic beads according to the present invention, exhibits disadvantages in curing properties, adhesion, and scratch resistance.

[0135] (Industry availability)

[0136] This invention provides a UV-curable coating composition with excellent stain resistance, adhesion, gloss, workability and scratch resistance.

Claims

1. A UV-curable coating composition comprising a trifunctional urethane (meth)acrylate oligomer, a trifunctional or higher-functional (meth)acrylate monomer, a difunctional (meth)acrylate monomer, a monofunctional (meth)acrylate monomer, ceramic beads, and a photoinitiator. The weight-average molecular weight of the trifunctional urethane (meth)acrylate oligomers is 800 to 3,000 g / mol. The ceramic beads have an average particle size of 7 to 13 μm.

2. The UV-curable coating composition according to claim 1, wherein, The viscosity of the trifunctional urethane (meth)acrylate oligomer is 500 to 3,000 cps at 25°C.

3. The UV-curable coating composition according to claim 1, wherein, The trifunctional or higher-functional (meth)acrylate monomers have a molecular weight of 100 to 500 g / mol and a viscosity of 50 to 300 cps at 25°C. The difunctional (meth)acrylate monomer has a molecular weight of 150 to 450 g / mol and a viscosity of 5 to 30 cps at 25°C. The monofunctional (meth)acrylate monomer has a molecular weight of 50 to 300 g / mol and a viscosity of 5 to 25 cps at 25°C.

4. The UV-curable coating composition according to claim 1, wherein, The trifunctional or higher (meth)acrylate monomers, the difunctional (meth)acrylate monomers, and the monofunctional (meth)acrylate monomers are used in a weight ratio of 1:0.2 to 1:2 to 5.

5. The UV-curable coating composition according to claim 1, wherein, The ceramic beads are alkali aluminosilicate ceramic beads.

6. The UV-curable coating composition according to claim 1, wherein, Relative to the total weight of the coating composition, the UV-curable coating composition comprises 30 to 60% by weight of the trifunctional urethane (meth)acrylate oligomer, 2 to 15% by weight of the trifunctional or higher (meth)acrylate monomer, 1 to 10% by weight of the difunctional (meth)acrylate monomer, 10 to 40% by weight of the monofunctional (meth)acrylate monomer, 1 to 8% by weight of the ceramic beads, and 0.01 to 10% by weight of the photoinitiator.

Citation Information

Patent Citations

  • Photosensitive composition comprising polyurethane prepolymer

    US3782961A

  • Photopolyer composition containing a polyurethane binding agent

    US3912516A